THE STUDY OF THE SCIENCE OF SOFT SKILLS AND ITS IMPACT ON THE LIVES OF UNDER GRADUATE STUDENTS IN MUMBAI (International Journal of Food and Nutritional Sciences, 2022)
Employability, the quality of being suitable for paid work, is the newly coined word for organisations and colleges today. This means that when a student graduates it is presumed that the theoretical knowledge is there however it does not necessarily mean that the student is Employable.Soft skills like Communication, Motivation, Teamwork, Leadership, etc. help bridge the gap in order to achieve success. It is these skills which will complement the theoretical and technical training that they are already receiving. A couple of decades ago it did not matter whether a graduating student could communicate well or not. The lack of soft skills in the current candidates has resulted in low hiring and promotions by corporates in India.Despite of this knowledge, many colleges are reluctant to incorporate soft skills training on a more regular and formal basis for their students. Although the theory component of their syllabi covers parts of communication and teamwork there is a dearth of formalised Soft Skills Training for the students.In this paper the researcher has tried to address the science of Soft skills and the positive impact of soft skills training on the lives of students. An educator has the opportunity to train the student in soft skills only during their lifespan in college.By identifying the areas of soft skills which a student has trained in, my study attempts to understand its importance on a deeper level. It also identifies the role of a teacher in imparting Soft skills training through various co-curricular activities.The researcher evaluates the deficit in various soft skills by collecting primary data from corporates, teachers and students.